Pengaruh Kegiatan Finger Painting Terhadap Perkembangan Motorik Halus Anak Pra Sekolah Di Pendidikan Aanak Usia Dini (PAUD) Melati Kota Padang - AYU, FIRDA DAMBA; Eliwarti (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2024)
Fine motor development is a limited movement of parts that include small muscles, especially movements in the fingers. According to the World Health Organization (WHO), more than 200 million preschool children under the age of 5 in the world do not meet their development potential, in Indonesia between 13% -18%. The rate of developmental delay in children is 5-25% of preschool children suffer from fine motor development disorders, (Ministry of Health of the Republic of Indonesia, 2021). This type of research is Quasi-experimental with a one group pretest and posttest design approach. This research was conducted at Early Childhood Education (PAUD) Melati, Padang City in 2024 from April to August 2024. The sampling technique using the Total sampling method consisted of one group, namely the experimental group with a sample size of 18 respondents. With the instrument used the Denver Development Screening Test (DDST), The results of the statistical test using the Wilcoxon signed rank test, the p-value/sig was 0.002 (p <0.05), it can be concluded that there is a significant difference in the motor development of preschool children before and after being given finger painting activities.